PI3K/AKT/PTEN Signaling as a Molecular Target in Leukemia Angiogenesis. (28th February 2012) - Okumura, Naoko; Yoshida, Hitomi; Kitagishi, Yasuko; Murakami, Mutsumi; Nishimura, Yuri; Matsuda, Satoru
Abstract : PI3K/AKT/PTEN pathway is important in the regulation of angiogenesis mediated by vascular endothelial growth factor in many tumors including leukemia. The signaling pathway is activated in leukemia patients as well as leukemia cell lines together with a decrease in the expression of PTEN gene. The mechanism by which the signaling pathway regulates angiogenesis remains to be further elucidated. However, it has become an attractive target for drug therapy against leukemia, because angiogenesis is a key process in malignant cell growth. In this paper, we will focus on the roles and mechanisms of PI3K/AKT/PTEN pathway in regulating angiogenesis.